2020
DOI: 10.1113/ep088203
|View full text |Cite
|
Sign up to set email alerts
|

The role of carotid bodies in the generation of active inspiratory and expiratory responses to exercise in rats

Abstract: Exercise involves the interaction of several physiological processes, in which adjustments in pulmonary ventilation occur in response to increased O 2 consumption, CO 2 production and altered acid-base equilibrium. The peripheral chemoreceptors (carotid bodies; CBs) are sensitive to changes in the chemical composition of arterial blood, and their activation induces active inspiratory and expiratory responses. Herein, we tested the hypothesis that the CBs contribute to the active inspiratory and expiratory resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 84 publications
(154 reference statements)
0
6
0
Order By: Relevance
“…This is relatively short which is important as it prevents large changes in PP which causes mechanical instability and loss of whole cell neuronal recordings. Several previous studies demonstrated that bilateral denervation of carotid body chemoreceptors abolished the respiratory, sympathetic, and cardiovascular responses to KCN at this concentration in vivo and in situ 33–35 …”
Section: Methodsmentioning
confidence: 68%
“…This is relatively short which is important as it prevents large changes in PP which causes mechanical instability and loss of whole cell neuronal recordings. Several previous studies demonstrated that bilateral denervation of carotid body chemoreceptors abolished the respiratory, sympathetic, and cardiovascular responses to KCN at this concentration in vivo and in situ 33–35 …”
Section: Methodsmentioning
confidence: 68%
“…If similar synergistic interaction applies to respiratory motor control during intense whole body exercise, the selective carotid body contribution to exercise hyperpnoea may be less than that evident in the study by Spiller et al. (2020). Nevertheless, whatever the nature of that potential interaction, there is a substantive role for carotid body feedback in the manifestation of the full hyperpnoeic response to exercise, at least in rats.…”
mentioning
confidence: 70%
“…Synergistic interaction between the muscle metaboreflex and the central chemoreflex has been shown in humans using post-exercise cuff occlusion to activate muscle afferents (Alghaith, Balanos, Eves, & White, 2019). If similar synergistic interaction applies to respiratory motor control during intense whole body exercise, the selective carotid body contribution to exercise hyperpnoea may be less than that evident in the study by Spiller et al (2020). Nevertheless, whatever the nature of that potential interaction, there is a substantive role for carotid body feedback in the manifestation of the full hyperpnoeic response to exercise, at least in rats.…”
mentioning
confidence: 89%
See 2 more Smart Citations